IMPLEMENTASI PROGRAM “ARKA” DALAM PENGUATAN PENDIDIKAN KARAKTER MELALUI PROYEK EMPATI DAN REFLEKSI TERARAH DI SEKOLAH DASAR - Niken Larasati; Wildan Nurul Fajar (STKIP Subang, 2026)
This study aims to describe the design process, implementation, and impact of the ARKA Program (Aksi dan Refleksi) as a character education innovation in Grade IV of SD Negeri Gandrungmangu 01. The research was grounded in the gap between students’ cognitive understanding of character values and their internalization into real behavior, compounded by limited parental guidance at home. A qualitative approach with a single case study design was employed. Data were collected through participant observation, document analysis of daily reflection journals and weekly character checklists, unstructured interviews, and field notes, then analyzed using the interactive model of Miles, Huberman, and Saldana. The ARKA Program integrates two main components: Empathy Action, comprising concrete activities such as peer tutoring, collaborative group work, and classroom cleaning; and Character Reflection, consisting of daily journal writing guided by structured questions. Findings indicate that the program produced consistent positive behavioral changes across five character dimensions simultaneously, including social care, cooperation, responsibility, discipline, and self-confidence. These changes were marked by a motivational shift from external compliance toward intrinsic moral awareness, as reflected in students’ increasingly expressive and reflective journal narratives. The program’s effectiveness is explained through the synergy of Bandura’s social learning theory, Kohlberg’s moral development theory, Dewey’s reflective learning theory, Lickona’s character education framework, and Deci and Ryan’s self-determination theory. The ARKA Program proves to be a simple, contextual, and replicable innovation model for elementary school teachers.